Persicimonas caeni gen. nov., sp. nov., the Representative of a Novel Wide-Ranging Predatory Taxon in Bradymonadales - Wang, Shuo; Mu, Dashuai; Du, Zong-Jun (Frontiers in Microbiology, 2020)
A novel bacterial strain, designated YN101T, was isolated from a marine solar saltern in the coast of Weihai, Shandong Province, China. Strain YN101T was Gram-stain negative, facultatively anaerobic, oxidase and catalase negative bacterium with the ability to prey on other microbes. A cross-streaking culture method was utilized to analyze the predatory activity of strain YN101T. The results showed strain YN101T could prey on various bacteria, either Gram-stain negative or Gram-stain positive. According to the predatory assays, different species in the same genus may behave differently when attacked by strain YN101T. The predatory behavior of strain YN101T to four typical species was analyzed, and furthermore, predation to Algoriphagus marinus am2T were quantitively studied by fluorogenic quantitative PCR, and the gene copies decreased over two magnitudes. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain YN101T shared the greatest sequence similarity of 93.9 % to Bradymonas sediminis FA350T. The complete genome sequence of strain YN101T was 8,047,306 bp in size and the genomic DNA G + C content was 63.8 mol%. The digital DNA-DNA hybridization (dDDH) values and average nucleotide identity (ANI) values between strain YN101T and B. sediminis FA350T were 13.9 % and 74.0 %. The genetic features showed that the biosynthesis of many important compounds was deficient in genome of strain YN101T, which may lead to its predation. Moreover, its genome encoded many genes affiliated with type IV pili, secretion system, membrane proteins and transduction proteins. Similar with myxocobateria and Bdellovibrio and like organisms (BALOs), these genes should play important roles in motility, adhesion or virulence to attack prey cells during predation. The predominant polar lipid profile of strain YN101T consisted of phosphatidylethanolamine (PE), phosphatidylglycerol (PG), diphosphatidylglycerol (DPG) and one unidentified aminophospholipid (APL). The major cellular fatty acid of strain YN101T was iso-C17:0, and the sole respiratory quinone was MK-7. Based on the chemotaxonomic, physiological and biochemical characteristics, strain YN101T represents a novel species of a novel genus in the family Bradymonadaceae, for which the name Persicimonas caeni gen. nov., sp. nov. is proposed. The type strain is YN101T (= KCTC 72083T = MCCC 1H00374T).